1983
DOI: 10.1021/bi00278a008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complementary deoxyribonucleic acid and gene coding for human prothrombin

Abstract: The DNA sequences of a complementary deoxyribonucleic acid (cDNA) and a portion of the gene coding for human prothrombin have been determined. The cDNA was 2005 base pairs in length and was found to code for part of a leader sequence of 36 amino acids, 579 amino acids present in the mature protein, a stop codon, a noncoding region of 97 base pairs, and a poly(A) tail of 27 base pairs. It is proposed that the leader sequence consists of a signal sequence and a pro sequence for the mature protein that circulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
184
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(203 citation statements)
references
References 51 publications
17
184
2
Order By: Relevance
“…3A). This pseudo-serine protease domain of factor D was more closely related to the catalytic domains of human tissue plasminogen activator [22] (31.7% identity) and also human plasmin [23] (29.4%) than to those of human Cls [24] (27.9%) and human thrombin [25] (23.3%). Among four serine proteases involved in the horseshoe crab coagulation cascade, the sequence of factor D showed the highest similarity with that of the clotting enzyme [26] (31.7%).…”
Section: Sequence Similarity To Other Proteinsmentioning
confidence: 99%
“…3A). This pseudo-serine protease domain of factor D was more closely related to the catalytic domains of human tissue plasminogen activator [22] (31.7% identity) and also human plasmin [23] (29.4%) than to those of human Cls [24] (27.9%) and human thrombin [25] (23.3%). Among four serine proteases involved in the horseshoe crab coagulation cascade, the sequence of factor D showed the highest similarity with that of the clotting enzyme [26] (31.7%).…”
Section: Sequence Similarity To Other Proteinsmentioning
confidence: 99%
“…2 This mutation is a G3A transversion at position 20210, the accepted prothrombin messenger RNA (mRNA) polyadenylation site. 3 Heterozygotes for the 20210A gene variant express prothrombin at levels that are about 25% higher than average. 1,4,5 The physiological importance of the 20210A mutation is evidenced by the significant risk of venous 1,6 and arterial thromboembolism 5,7,8 displayed by 20210G/A heterozygotes, which can be particularly severe in specific subpopulations and target organs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] These discoveries confirmed that the coagulation proteins were derived from genes which encoded modular domains that were shared between related families of coagulation factors (eg, the vitamin K-dependent factors and factors V and VIII). Soon after the cloning of the FVIII and FIX genes, translational application of this knowledge was initiated through the introduction of molecular diagnostics, 12 the development of recombinant clotting factors for replacement therapy, 13 and the initial preclinical trials of gene therapy.…”
Section: Gene Therapy Concepts and Historical Contextmentioning
confidence: 66%